Chemical Characteristics of Scales, Skin And Bones of Snakehead Fish (Channa Striata) After Soaked With Sodium Hydroxide Solution - Herpndi; Muliajaya, Fitra; Pratama, Filli; Widiastuti, Indah (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
Snakehead fish is one of the freshwater products that has potential in South Sumatra. Utilization of snakehead fish as a side dish and diversification product is for typical Palembang food processing. Most of these preparations used meat as a raw material, leaving waste scales, skin and bones which had the potential to be used as raw materials for collagen. One of the stages of collagen production was soaking in NaOH. The aim of this research was to examine the chemical properties of scales, skin and bones of snakehead fish after soaking in NaOH. The soaking process was carried out in 0.05M NaOH for 6 hours and the water was changed every 2 hours with a ratio of waste to NaOH solution of 1:10. The parameters analyzed included water content, ash content and protein. The results showed the proportion of scales, skin and bones of snakehead fish respectively of 6% scales, 5.7% skin and 4.20% bones. Proximate analysis tests showed levels in snakehead fish scales of 55.67%, skin by 81.15% and bones by 50.80%. The average value of ash content was in snakehead fish scales of 48.14%, skin by 9.27% and bones by 55.42%. The average value of protein content was in snakehead fish scales by 29.60%, skin by 67.59% and bones by 23.66%.